Customer Participation Behaviour and Brand Equity: The Moderating Role of Fraud Prevention in Digital Banking - Iram Arshad; Dr. Ejaz Ahmed; Hafiz Muhammad Hanif; Faiz Rasool Zaka (`, 2026)
The online shift in the banking sector makes more consumers desire online services. Consequently, the participation opportunities are increased, yet the amount of fraud is also higher. Two are important motives, which are securing the value of the brand and ensuring security through the customer participation behavior (CPB). We consider the Pakistani banking industry and the role of fraud prevention (FP) between customer participation behavior (CPB) and brand equity (BE) in this study. The Unified Theory of Acceptance and Use of Technology (UTAUT) demonstrates that consumer involvement is one of the driving forces of secure digital interactions and strategic brand progress based on the study. The study employs structural equation modelling as the method of testing the alleged relationships based on survey data of consumers of digital banks. With the introduction of fraud protection to the customer-brand structure, the study contributes conceptual richness to the current body of literature on co-creation of services and branding. It tells banks in poor nations how to use participatory fraud prevention tactics to establish trust, retain people engaged, and strengthen their brand positioning. Keywords: Customer participation, fraud prevention, brand equity, digital banking, Pakistan, UTAUT https://doi.org/10.5281/zenodo.18317380